Evaluation of the Cases Admitted to the Disability Board After A Traffic Accidental Head Trauma, in Terms of Neuropsychiatric Sequelae - Ünaldı, Şeyma Tuğçe; Poyraz, Turan; Bora, İbrahim Emre and Can, İsmail Özgür (The Bulletin of Legal Medicine, 2023)
Objective: Trauma is the most important cause of death in underdeveloped and developing countries. Although the brain has protective layers such as the cranium and scalp, it can be damaged as a result of various traumas, causing permanent neurological and psychiatric sequelae. In our study, we aimed to evaluate the demographic data of patients who applied to our department to be evaluated in terms of disability after head trauma due to a traffic accident, and to emphasize that objective data criteria are required in the evaluation of neuropsychiatric sequelae. Methods: Sociodemographic characteristics, neuropsychiatric complaints, neuropsychological testing results and disability rate/duration of patients evaluated in the disability board of our department between 01.01.2019-31.12.2020. Results: It was observed that 579 of the patients investigated during the study period had head trauma. It was observed that 173 of 579 patients had intracranial injury and neuropsychiatric sequelae and a related disability rate was determined. 79.2% of the cases were male, 20.8% were female, the mean age was 29.6±15.6. Most common symptoms were dementia in 113 cases (65.3%), headache in 60 cases (34.6%) and psychiatric complaints in 48 cases (27.7%). Conclusion: As a result of the study, it was seen that neuropsychiatric sequelae due to head trauma are quite common and varied. The severity of the trauma and clinical situation should be determined by objective criteria. Detailed examination, neuropsychological testing and radiological examinations will prevent such cases from being overlooked.